Herpesvirus Infections After Chimeric Antigen Receptor T-Cell Therapy and Bispecific Antibodies: A Review - Joseph Sassine; Emily A. Siegrist; Roy F. Chemaly (Viruses)
In this narrative review, we explore the burden and risk factors of various herpesvirus infections in patients receiving chimeric antigen receptor T-cell (CAR-T) therapy or bispecific antibodies (BsAb) for the treatment of hematologic malignancies. Antiviral prophylaxis for herpes simplex/varicella zoster viruses became part of the standard of care in this patient population. Breakthrough infections may rarely occur, and the optimal duration of prophylaxis as well as the timing of recombinant zoster immunization remain to be explored. Clinically significant cytomegalovirus (CMV) infections can affect up to 10% of patients after CAR-T, depending on the CAR-T product target, post-CAR-T complications such as cytokine release syndrome and the need for glucocorticoid therapy. Surveillance and prophylactic strategies for CMV need to be developed, whereas the risk factors for and the burden of CMV infections after BsAb are not yet well-defined. Human herpes virus 6 reactivation and end organ disease such as encephalitis are rarely reported after CAR-T and have not yet been reported after BsAb; additional research is needed.